ADSORPTION RATE CONSTANTS OF EOSIN IN HUMIN - Andi Muhammad Anshar; Santosa S.J; Sudiono S (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
Eosin is one of the dyes commonly used in the industry and has the potential to cause pollution of the water environment. The Eosin pollution treatment methods used in this study was the adsorption method using humin fraction obtained from the peat land comes from Kalimantan. From the research data showed that the adsorption of eosin in humin result of washing with HCl / HF optimum at pH 4 and a contact time of 60 minutes with the adsorption-order rate was 8,4 x 10-3 min-1